DNA hybridization at microbeads with cathodic stripping voltammetric detection - Palecek, E; Billová, S; Havran, L; Kizek, R; Miculková, A; Jelen, F (Talanta, 2002)
In electrochemical DNA hybridization sensors generally a single-stranded probe DNA was immobilized at the electrode followed by hybridization with the target DNA and electrochemical detection of the hybridization event at the same electrode. In this type of experiments nonspecific adsorption of DNA at the electrode caused serious difficulties especially in the case of the analysis of long target DNAs. We propose a new technology in which DNA is hybridized at a surface H and the hybridization is detected at the detection electrode (DE). This technology significantly extends the choice of hybridization surfaces and DEs. Here we use paramagnetic Dynabeads Oligo(dT)(25) (DBT) as a transportable reactive surface H and a hanging mercury drop electrode as DE. We describe a label-free detection of DNA and RNA (selectively captured at DBT) based on the determination of adenines (at ppb levels, by cathodic stripping voltammetry) released from the nucleic acids by acid treatment. The DNA and RNA nonspecific adsorption at DBT is negligible, making thus possible to detect the hybridization event with a great specificity and sensitivity. Specific detection of the hybridization of polyribonucleotides, mRNA, oligodeoxynucleotides, and a DNA PCR product (226 base pairs) is demonstrated. New possibilities in the development of the DNA hybridization sensors opened by the proposed technology, including utilization of catalytic signals in nucleic acid determination at mercury (e.g. signals of osmium complexes covalently bound to DNA) and solid DEs (e.g. using enzyme-labeled antibodies against chemically modified DNAs) are discussed.